Innovasi Produk Mie Kering Non Gluten dari Ubi Ungu Di Desa Tabalagan Kabupaten Bengkulu Tengah - Prasetya, Andwini; Arif, Hilda Meisya; Antinka, Vineza Elsafa; Utami, Wahyu (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
Community service on this product innovation with purple sweet potato substitution as an ingredient for making dry noodles which aims to; improve malnutrition in children in central Bengkulu with the characteristics of purple sweet potatoes which have high enough fiber and can be substituted into making dry noodles and are functional foods containing beta-carotene which functions to maintain healthy skin and eyes. The service was carried out by students and lecturers of the faculty of agriculture and audiences from PPK mothers and fathers of the tabalagan village community. After this community service, the community can make dry noodles as an ingredient to overcome malnutrition that occurs in Central Bengkulu, Tabalagan village